Guiding the sustainable management of rice landscapes in the uplands - Pandey, S. (2009)
For the 20 million people whose livelihood directly depends on land and water resources in upper catchments of the Mekong and the Red River basins, improving the productivity of rice could help to break the cycle of poverty, food insecurity and environmental degradation that characterizes the area. Farmers living in these catchments are extremely poor, their main agricultural activity consisting of producing rice and other food items for house hold consumption. Increasingly population pressure has forced many farmers onto marginal agricultural land, particularly steep sloping land where land use practices are contributing to soil erosion and water losses. The high incident of poverty in this area often directly correlates with the degree of rice self-sufficiency. Helping farmers produce rice more productively is a key entry point for converting the vicious cycle of law poverty-environmental degradation into a virtuous cycle that raises productivity, increases income and protects and the environment.